Damage assessment on the discarded macro-benthic fauna in the Italian striped venus clam (Chamelea gallina) fisheries - BARGIONE, GIADA; GUICCIARDI, STEFANO; VIRGILI, MASSIMO; BARONE, GIULIO; LUCCHETTI, ALESSANDRO (Mediterranean Marine Science, 2024)
The striped venus clam fishery in Italy is carried out by means of hydraulic dredges and it is one of the most important socio- economic activities in the Italian fisheries sector. Dredging has traditionally been considered among fishing activities with the greatest impact at the ecosystem level. Here, therefore, we investigated the disturbance level exerted by dredging on the studied area. Also, damage and mortality rates exerted by dredging on the discarded macro-benthic fauna living associated with Chamelea gallina during the summer season were investigated using a four-level damage scale, given three different haul time duration (3, 6 and 9 minutes). Despite the fact that macro-benthic fauna represented on average only 4.4% of the total catch, the most represented taxa in terms of both abundance and number were Malacostraca, Bivalvia, and Echinoidea. The analysis of the macro-benthic communities’ structure between hauls revealed that the species composition was very similar, and ABC plots together with the Warwick Statistics (W) revealed a moderately disturbed macro-benthic community. No significant difference was found in damage and mortality rates between hauls duration when stratified at taxon or species level. Overall, 61.0% of individuals of the catch were undamaged, whereas 16.1%, 3.7%, and 19.2% displayed slight, intermediate, and severe damage, respectively. We found that soft-shelled or soft-bodied species were the most affected by the harvesting process, whereas thick-shelled or thick-bodied species suffered the slightest damage. In particular, the species suffering major (severe) damage were the sea urchin Echinocardium cordatum (84.6%), the bivalves Mactra stultorum and Polititapes aureus (32.5% and 20.0%, respectively), the crab Liocarcinus vernalis (4.0%), and the sea star Astropecten irregularis (4.8%). The overall mortality rate of all discarded individuals was 22.9%, with E. cordatum showing the highest mortality rate of 96.0%. These findings highlight the importance of guaranteeing the integrity of the entire ecosystem through the adoption of suitable management plans and actions.